Evaluation of antibiotic prescription in the Lebanese community: a pilot study - Nadine Saleh; Sanaa Awada; Rana Awwad; Sahar Jibai; Chadi Arfoul; Liliana Zaiter; Wissam Dib; Pascale Salameh (Infection Ecology & Epidemiology, 2015)
Background: Antibiotics are considered among the most commonly prescribed drug classes in developing countries. Inappropriate prescription of antibiotics is a major public health concern and is related to the development of antimicrobial resistance. Objective: This study aimed at assessing the appropriateness of antibiotic prescription by non-infectious disease physicians in a community setting in Lebanon. Methods: A pilot cross-sectional study was undertaken on community pharmacy patients presenting with antibiotic prescription. It was performed over a period of 4 months in different regions of Lebanon. Participants answered a questionnaire inquiring about socio-demographic characteristics, medical conditions, symptoms that required medical attention, the doctor's diagnosis, the prescribed antibiotic, and whether laboratory tests were ordered to identify the causative organism or not. Data were analyzed using SPSS 17. Results: We studied 270 patients (49.3% males and 50.7% females). This study showed that the most-prescribed antibiotics were the cephalosporins (82%) and that almost half of the illnesses for which antibiotics were prescribed were respiratory tract infections (41%). The study also showed that the choice of the prescribed antibiotic was appropriate in 61.5% of the studied cases, while the prescribed dose and the duration of the treatment were inaccurate in 52 and 64% of the cases, respectively. In addition, fever seemed to be a factor that influenced the physician's prescriptions, since the choice of drug conformity to guidelines increased from 53.7% (1 day of fever) to 88.9% (1 week of fever), and the dose prescription compliance to guidelines was higher (55.9%) for patients suffering from fever compared to those with no fever (38.1%). Conclusion: This study showed a high prevalence of inappropriate antibiotic prescriptions in Lebanon. Therefore, actions should be taken to optimize antibiotic prescription.